Hybrid cellulose nanocrystals and graphene oxide polysulfone membranes for copper removal - Siti Nurul Najiah, Abd Rasid; Nor Azura, Che Mahmud; Syed Mohd, Saufi; Takriff, Mohd Sobri; Ang, Wei Lun (Desalination Publications, 2022)
Polysulfone (PSF) membranes blended with cellulose nanocrystals (CNC) and graphene oxide (GO) nanofiller were prepared for copper removal in this study. The impacts of single CNC, GO, and mixed CNC-GO addition on the morphology, hydrophilicity, permeability, copper ion rejection, and membrane binding capacity were discussed. Scanning electron microscopy results showed that incorporating CNC, GO, and CNC-GO resulted in a more porous membrane structure with a high porosity value. The hydrophilicity of hybrid CNC-GO-PSF membranes were improved with the increment of CNC content and inclusion of the GO filler. Hybrid membranes showed a significant increment of flux compared to pristine PSF membrane. The water flux of the hybrid P-1GO-2C membrane is 8-fold higher than the pure PSF membrane (3.31 L/m2•h). However, the copper rejection of the hybrid CNC-GO-PSF membranes was less than 50%. The increment of the CNC in the hybrid CNC-GO-PSF membrane increases the membrane porosity, and the sub-layer structure of the membrane is becoming very loose. In adsorptive filtration mode, the GO-PSF membrane showed the highest copper binding capacity of 8.49 mg•Cu/g membrane.